Intermedialität in der Frühen Neuzeit: Formen, Funktionen, Konzepte - Robert, Jörg (Frühe Neuzeit, 2017)
"In recent years, intermediality has become a paradigm in literary studies, the visual arts, and musicology. This interdisciplinary volume presents a first attempt to systematically apply the forms, functions, and concepts of intermediality to the Early Modern Period. In addition to addressing forms of literature-centered intermediality, the work focuses on varieties of musical intermediality and the concept of the artistic work as a whole"--